(untitled) (Italiano LinguaDue, 2022)
Il presente articolo illustra la storia dell’insegnamento della lingua italiana nella Repubblica Popolare Cinese, con particolare riferimento alle testimonianze raccolte dal 1962 al 2022 nel Dipartimento di italiano della Beijing Foreign Studies University, una delle prime università cinesi ad insegnare la lingua e la letteratura italiana. Utilizzando le fonti archivistiche dell’Ateneo e le fonti orali dei testimoni, l’autrice ricostruisce la storia del sopracitato Dipartimento in tre fasi, in stretto contatto con l’ambiente cinese e con il contesto del rapporto tra Italia e Cina, sottolineando in ogni fase gli aspetti connessi alle condizioni di ammissione degli studenti, della qualificazione dei docenti, dei lavori lessicografici, dei materiali didattici e delle metodologie glottodidattiche. Teaching Italian language in the people’s republic of China: a case study at the department of Italian at Beijing foreign studies university between 1962 and 2022 This paper illustrates the history of Italian language teaching in the People’s Republic of China, with particular reference to evidence gathered from 1962 to 2022 at the Department of Italian at Beijing Foreign Studies University, one of the first Chinese universities to teach Italian language and literature. Using the archival sources of the University and the oral sources of witnesses, the author reconstructs the history of the aforementioned Department in three phases, in close contact with the Chinese environment and within the context of the relationship between Italy and China, emphasizing in each phase the aspects related to the conditions for the admission of students, the qualification of teachers, lexicographic works, teaching materials and language teaching methodologies.